Passive Electronic Componets Parameters Searching with Differential Evolutionary Algorithm - Juraj Palecek; Martin Vestenicky (Communications - Scientific letters of the University of Zilina, 2011)
This paper describes computing of inductor parameters as passive electronic component with algorithm of differential evolution. Computing of parameters is based on substitute model of inductor which is described with three basic parameters such as resistance, inductance and capacitance. Measured frequency response of complex impedance of the real inductor is input parameter to the iterative loop driven by the differential evolution algorithm. There are three output parameters of the algorithm, where resistance value is considered to be a combination of DC coil resistance and skin effect influence, second value describes inductance of a real inductor and third parameter defines interturn parasitic capacitance of a real inductor.